Combined toxicity of graphite-diamond nanoparticles and thiabendazole to Daphnia magna - Martín-de-Lucía, Idoia (2019)
Carbon-based nanomaterials exhibit unique properties that make them suitable for a wide variety of industrial and biomedical applications. In this work, we studied the acute toxicity of graphite-diamond nanoparticles (GDN) combined with the fungicide thiabendazole (TBZ) to the immobilization of the cladoceran Daphnia magna in the presence and absence of the micro green algae Raphidocelis subcapitata, supplied as food source. The toxicity of GDN to D. magna decreased in the presence of R. subcapitata, while that of TBZ increased, the latter suggesting a carrier effect to TBZ. GDN-TBZ mixtures were fitted to the most common conceptual models applied to mixture toxicity: Concentration Addition (CA), Independent Action (IA) and Combination Index (CI). For GDN-TBZ mixtures in the absence of food the best fit was obtained with dose ratio deviation from CA model, while in the presence of food, dose level deviation from CA gave a better fit. The binary mixtures of GDN and TBZ showed synergistic toxic interactions at low concentrations, which could be attributed to the increased bioavailability of TBZ adsorbed on GDN. For higher concentrations of GDN, the binary mixtures turned antagonistic due to particle agglomeration. Our study provides evidence that deviations from additivity are dose dependent and relevant for the risk assessment of mixtures of nanoparticles with other chemical pollutants.